Survei Minat Siswa Dalam Pembelajaran PJOK Di Masa Pandemi Covid-19 Siswa Kelas XI SMA Negeri 3 Bangkalan - Khoirul Anwar; Ihwan Firmansyah (Jendela Olahraga, 2022)
The balance between cognitive, affective and psychomotor directs learning objectives at optimal development. Of course, the achievement of learning outcomes still pays attention to the supporting and inhibiting factors that surround both the teacher and the students. In this study, researchers wanted to find out where the student's lack of interest in PJOK learning during the COVID-19 Pandemic was as an effort to evaluate the learning outcomes that had been carried out. The researcher chose the most appropriate approach to carry out this research, namely quantitative research with a descriptive approach. The questionnaire instrument was used to measure how much students were interested in PJOK learning during the Covid-19 pandemic. The validity test was tested on 25 respondents, which means that if it exceeds the R table, which is 0.395, it is said to be valid. The validity of this research has been set from 20 questions to 13 valid questions. Cronbach's Alpha value is at 0.733. The results of the research students did not like PJOK learning which was carried out online. This can be interpreted that learning sports as learning that requires active movement is less effective if carried out using online methods. Students stated that they strongly disagreed that learning was carried out with zoom (64.9% disagreed), youtube media (59.4% disagreed), and google classroom (52% disagreed) this could mean that the media did not can accommodate the psychomotor aspect of students to be able to move directly to practice the material being taught. The conclusion of the research is that students' interest is moderate. The advice that can be given is to keep exploring various online learning media to improve the quality of subjects.